The COVID-19 pandemic related stress and the associated factors among the healthcare workers in Kota Setar District Health Office, Malaysia - Itam, Mohd Faiz; Minhat, Halimatus Sakdiah; Abd Rahman, Anita; Ibrahim, Mohd Zukri; Shareh Ali, Shareh Azizan; Shuhaimi, Ahmad Hanis (Public Library of Science, 2024)
Background The COVID-19 pandemic is the most significant worldwide health catastrophe, with massive impacts observed particularly among the healthcare workers. Stress among healthcare workers is a significant and pervasive issue that can have profound implications for both the well-being of healthcare professionals and the quality of patient care. This study aimed to determine the prevalence of stress related to the COVID-19 pandemic and the associated factors among the healthcare workers (HCWs). Methods A retrospective cross-sectional study was conducted involving 533 HCWs in Kota Setar District Health Office. Related data was collected between January and June 2021. Stress was measured using the Depression Anxiety Depression Scale 21 (DASS-21). Other variables included in this study were sociodemographic and employment factors. The associated factors and predictors were determined by employing chi-square test and multivariate logistic models. Results COVID-19 related stress was reported at 10.5%. HCWs who work at the district health offices and those with degree or higher qualifications had 2.3 (AOR = 2.310, 95% CI: 1.177–4.535) and 3 (AOR = 2.899, 95% CI: 1.613–5.211) higher odds of experiencing stress compared to those working in the clinics and had lower qualifications (diploma or less). Conclusions The mental wellbeing of the HCWs participated in this study had been affected negatively by the COVID-19 pandemic, resulting in one in 10th of the HCWs were experiencing stress during the COVID-19 pandemic, with higher risk observed among those working at the district health office and HCWs with higher qualifications or ranking. This is expected since COVID-19 was a new and unprecedented outbreak associated with massive number of mortalities that requires active contact tracing and surveillance which commonly conducted at district health office level. Active intervention needed to cope with the overwhelming stress and working condition to ensure effective rehabilitation are in place and quality of work were not jeopardized.